Vascular flow density in pathological myopia: an optical coherence tomography angiography study - Mo, Jing (BMJ Open, 2017)
OBJECTIVES: To investigate vascular flow density in pathological myopia with optical coherence tomography (OCT) angiography. DESIGN: A prospective comparative study was conducted from December 2015 to March 2016. SETTING: Participants were recruited in Beijing Tongren Hospital. PARTICIPANTS: A total of 131 eyes were enrolled, which were divided into three groups: 45 eyes with emmetropia (EM; mean spherical equivalent (MSE) 0.50D to −0.50D), 41 eyes with high myopia (HM; MSE ≤−6.00D, without pathological changes), and 45 eyes with pathological myopia (PM; MSE ≤−6.00D and axial length (AL) ≥26.5 mm, and with pathological changes). MAIN OUTCOME MEASURES: Macular, choriocapillaris and radial peripapillary capillary (RPC) flow densities were measured and compared between groups, and their relationships with AL and best corrected visual acuity (BCVA) were analysed. RESULTS: Significant differences were found in macular, choriocapillaris and RPC flow densities among the three groups (p<0.05). Multiple comparisons revealed that, compared with the EM and HM groups, macular and RPC flow densities of the PM group were significantly decreased (p<0.05), but no significant difference in choriocapillaris flow density was found between the PM and HM groups (p=0.731). Compared with the EM group, retinal flow density in the macular and arcuate fibre region was not decreased in the HM group. In addition, there was a negative correlation between AL and superficial macular flow density (β=−0.542, p<0.001), deep macular flow density (β=−0.282, p=0.002) and RPC flow density (β=−0.522, p<0.001); and a positive correlation between BCVA and superficial macular flow density (β=0.194, p=0.021), deep macular flow density (β=0.373, p<0.001), and choriocapillaris flow density (β=0.291, p=0.001). CONCLUSIONS: Macular and RPC flow densities decreased in pathological myopia compared with high myopia and emmetropia. No significant decrease of retinal flow density in the macular and arcuate fibre region was found in high myopic eyes compared with emmetropic eyes. Moreover, macular and RPC flow densities were negatively related to AL, and macular flow density was positively related to BCVA.